Diseño de un sistema de protección de los generadores en conexión y no aterrizados para detectar fallas a tierra en la central hidroeléctrica “la península” perteneciente a la EEASA en el período agosto 2013 – agosto 2014 - Culqui Moposita, Wilson Tarquino (2015)
The design of the electrical protections made by computerized systems is necessary in a power generation as it receives all abnormal conditions in an electrical system. In much of electric generators such as La Peninsula belonging to the Utility Ambato EEASA have no system ground, this system was made for the generators out of operation as there is a ground fault and can continue to run, but if the fault persists healthy drivers would be subject to high voltages up to 1,73 times, this situation causes premature aging of the insulation system and a second failure will next time....